Etyczne problemy ochrony danych osobowych pracownika w stosunkach pracy - Nerka, Arleta (Annales. Etyka w Życiu Gospodarczym, 2010)
This study concerns the ethical problems of personal data protection at work. The aim of this project is the analysis of the law structures, which determine the range of protection personal data of the employee and the candidate to work and the rights of data collecting and processing by the employer. The employee privacy protection at work is the principle of labour law expressed in Article 11 of the Labour Code. However personal data protection problem is directly regulated by Article 22 of the Labour Code, which entitle employers to demand certain personal data from the employees and the candidates to work. The regulation determine the list of data, which may be the subject of legal actions by employer in the field of collecting and processing of personal data. The most important issue is connected with the treatment of sensitive information, such as health data, drug testing and genetic testing, sex life, racial or ethnic origin, political opinions, religious or philosophical beliefs, trade-union membership. Personal data protection means the necessity of cooperation between the employee and the employer not only in the field determined by the law but on the basis of ethical values as well. Hence the employer’s obligation to keep from actions which directly interfere in employee’s protected personal effects. But the employee is obliged to give true information about himself in order to protect his health and life at work.